Tracking of Dietary Patterns From Pregnancy to 6 Years Post-pregnancy in a Multiethnic Asian Cohort: The Growing Up in Singapore Towards Healthy Outcomes (GUSTO) Study. (7th June 2021) - Lee, Yu Qi; Colega, Marjorelee; Sugianto, Ray; Lai, Jun Shi; Godfrey, Keith M; Tan, Kok Hian; Shek, Lynette Pei-Chi; Loy, See Ling; Chan, Jerry Kok Yen; Müller-Riemenschneider, Falk; Padmapriya, Natarajan; Chan, Shiao-Yng; et al.
Abstract: Objectives: We assessed the stability of maternal dietary patterns from pregnancy to 6 years post-pregnancy and their associated-sociodemographic and lifestyle factors. Methods: At 26–28 weeks' gestation and 6 years post-pregnancy, 24-hour recalls and food frequency questionnaires were collected, respectively, from women in the GUSTO mother-offspring cohort ( n  = 709). Data on maternal sociodemographic and lifestyle factors were collected at recruitment and again during the 4 to 6-year follow-up visits. Dietary patterns were identified using principal component analysis and stability assessed using Pearson's correlation coefficients and Cohen's weighted kappa. Associations were assessed by multivariable logistic regression, with adjustment for covariates. Results: The 'Fruits, Vegetables and Legumes' (FVL) and 'Seafood, Noodle, Soup' (SNS) patterns were identified at both time points, with poor correlation for the dietary pattern z-scores (correlation coefficients: 0.2 and 0.3, respectively) and modest agreement in tertile assignment (weighted κ: 0.11 and 0.15, respectively), suggesting poor stability. An 'unhealthy' pattern was only observed at 6 years post-pregnancy. Women with only primary/secondary level education tended to decrease adherence to FVL pattern over time. Women who had gestational diabetes during pregnancy tended to maintain high adherence to FVL pattern over time. Other health conditions such as hypertension during pregnancy and post-delivery development of type 2 diabetes and hypertension did not appear to influence change in women's diet. Women who showed increased adherence to FVL pattern also exhibited healthy lifestyle behaviours, such as being more physically active, post-pregnancy. Women who adhered more closely to the 'unhealthy' pattern at 6 years post-pregnancy tended to be younger, of Malay ethnicity, had lower education, had lower household income at 5 years post-pregnancy, were less physically active and had additional pregnancies. Conclusions: Study findings may be used to inform the design of public health interventions for certain subgroups of women during pregnancy and at post-pregnancy that target key dietary and lifestyle risk behaviours. Funding Sources: Singapore Ministry of Health's NMRC, Singapore—NMRC/TCR/004-NUS/2008; NMRC/TCR/012-NUHS/2014, SICS, A*STAR, and MOE Academic Research Fund.